1990
DOI: 10.1161/01.hyp.15.5.514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin on renal sodium handling in hypertensive rats.

Abstract: Spontaneously hypertensive rats have reduced peripheral insulin sensitivity. To determine whether hypertensive rats demonstrate reduced response to the antinatriuretic effect of insulin, urinary sodium excretion was determined in hypertensive and normotensive rats (n=7 per group) before and during euglycemic insulin administration at two infusion rates (21 milliunits/kg load and 4 milliunits/kg/min or 85 milliunits/kg load and 8 milliunits/kg/min). Hypertensive and normotensive time controls received the vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0
4

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 15 publications
3
30
0
4
Order By: Relevance
“…Insulin increases sodium and water reabsorption in the proximal tubules of the kidney (22). Even with increased peripheral insulin resistance, as in hypertension (23) and obesity (24), the effect of insulin in the kidney seems to be preserved. Insulin also affects monoamine metabolism in the hypothalamus, resulting in increased sympathetic activity (25).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin increases sodium and water reabsorption in the proximal tubules of the kidney (22). Even with increased peripheral insulin resistance, as in hypertension (23) and obesity (24), the effect of insulin in the kidney seems to be preserved. Insulin also affects monoamine metabolism in the hypothalamus, resulting in increased sympathetic activity (25).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, insulin has been shown to reduce urinary sodium excretion by increased renal tubular sodium reabsorption [23]. It is unknown whether this antinatriuretic effect of insulin enhanced survival in our malnourished ancestors by promoting sodium preservation.…”
mentioning
confidence: 99%
“…Finally, a number of investigators have demonstrated that insulin resistance and hyperinsulinemia also are seen in spontaneously hypertensive rats. 28 " 30 In addition, insulinstimulated glucose uptake has been reported to be lower in adipocytes isolated from these animals. 29 Thus, based on this data it would appear that insulin resistance and hypertension are directly and possibly even causally related; however, data also suggest that the relation between insulin and hypertension is not so straightforward.…”
Section: -15mentioning
confidence: 96%